Local corporate taxation and business activity - Jacob Lundberg; Gabriella Massenz (Research Institute of Industrial Economics (IFN), 2025)
We use a natural experiment and administrative data to study the effect of corporate tax cuts on business activity. For identification, we exploit the abolition of municipal corporate income taxation in Sweden in 1985, which created variation in corporate tax changes faced by different municipalities. Our findings indicate an expansion of business activity and employment in large firms following a tax cut. However, we find no significant impact on these outcomes for small firms. In addition, firm entry rates increase in municipalities experiencing the largest tax cuts.
Keywords: G31; G38; H21; H25; 330; Corporate taxation; Business activity; Employment; Firm entry